2020
DOI: 10.3390/antibiotics9120844
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Conjugation Leads to Length-Dependent Antimicrobial Activity of a Synthetic Antibacterial Peptide (Pep19-4LF)

Abstract: The increasing number of infections caused by multidrug-resistant bacteria requires an intensified search for new antibiotics. Pep19-4LF is a synthetic antimicrobial peptide (GKKYRRFRWKFKGKLFLFG) that was previously designed with the main focus on high antimicrobial activity. The hydrophobic motif, LFLFG, was found to be essential for antimicrobial activity. However, this motif shows several limitations such as aggregation in biological media, low solubility, and small yields in peptide synthesis. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…As the lipidation of AMPs may have a significant effect on activity [ 17 ], we first investigated the effect of conjugating butanoic, hexanoic, octanoic, decanoic, lauric and myristic acids to BP214. The resulting C 4 , C 6 , and C 8 lipidated BP214 analogs (i.e., 1 – 3 ) showed a good activity (2–16 μg/mL) against the Gram-negative bacteria E. coli , K. pneumoniae , and A. baumanii , and a moderate activity against P. aeruginosa (32 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…As the lipidation of AMPs may have a significant effect on activity [ 17 ], we first investigated the effect of conjugating butanoic, hexanoic, octanoic, decanoic, lauric and myristic acids to BP214. The resulting C 4 , C 6 , and C 8 lipidated BP214 analogs (i.e., 1 – 3 ) showed a good activity (2–16 μg/mL) against the Gram-negative bacteria E. coli , K. pneumoniae , and A. baumanii , and a moderate activity against P. aeruginosa (32 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, multiple studies have found that coupling a fatty acid to antimicrobial peptides could modify both the activity and selectivity of the peptide and the length of the fatty acid was found to be directly correlated to the antimicrobial activity of fatty acid-conjugated antibacterial peptide [20][21][22]. Alexander et al detected the antimicrobial activity, structure, and solution assembly properties of peptide AKK conjugated with fatty acids of different carbon chain lengths, and the result showed that the antimicrobial activity of conjugated peptide increased with the fatty acids carbon chain lengths up to 16 carbons [23].…”
Section: Antimicrobial Activity In Vitromentioning
confidence: 99%
“…132 The shortening of fatty acid led to improved antimicrobial activity against Gram-positive bacteria and a lower hemolytic activity. 133 The improved antimicrobial activity was due to pore formation, micellization of the phospholipid bilayer and peptide aggregation. 132 Similarly, Stachuski et al showed the role of shortening of the fatty acid chain in improving the antimicrobial activity of lipopeptides.…”
Section: Amp-based Nanoformulations and Their Antimicrobial Propertiesmentioning
confidence: 99%